2019
DOI: 10.3390/medicina55100701
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Measurements in Standing Position with a Rebound Tonometer

Abstract: Background and Objectives: It has been established that body position can play an important role in intraocular pressure (IOP) fluctuation. IOP has been previously shown to increase significantly when lying down, relative to sitting; this type of investigation has not been extensively reported for the standing (ST) position. Therefore, this study aims to look for eventual significant IOP changes while ST, sitting, and lying down. Materials and Methods: An Icare PRO was used to measure the IOP of 120 eyes of 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…During the day, several people spend hours in the standing position, so it might be useful to know if a change in IOP occurs in this situation. In a previous paper, utilizing an I Care Pro (ICP) Tonometer, we were able to prove that both in the supine and in the standing position, there was an increase in IOP [ 9 ], but we were not able to find other studies that reported a comparison with other instruments, that confirmed such a finding in standing position. The IOP measurements are mainly performed with Goldmann applanation tonometry (GAT), which is nowadays considered the gold standard for these measurements, but this device can be used only with the patient seated at a slit lamp [ 10 ].…”
Section: Introductionmentioning
confidence: 71%
“…During the day, several people spend hours in the standing position, so it might be useful to know if a change in IOP occurs in this situation. In a previous paper, utilizing an I Care Pro (ICP) Tonometer, we were able to prove that both in the supine and in the standing position, there was an increase in IOP [ 9 ], but we were not able to find other studies that reported a comparison with other instruments, that confirmed such a finding in standing position. The IOP measurements are mainly performed with Goldmann applanation tonometry (GAT), which is nowadays considered the gold standard for these measurements, but this device can be used only with the patient seated at a slit lamp [ 10 ].…”
Section: Introductionmentioning
confidence: 71%
“…On a related matter, fitting actual sinusoidal functions to the data and utilizing the MESOR (rather than the arithmetic mean) of the data points also improved the robustness of the results, as the MESOR is not biased by the timing of the measurements. Third, our data collection methodology controlled or nullified as many confounding variables as possible during data collection, including strict exclusion criteria for visual function when selecting participants; carefully controlled lighting conditions during and between measurement epochs; ensuring that the participants remained seated throughout all epochs (to avoid possible effects of postural changes on measurements) 34 36 ; and preventing participants from engaging in any near-distance tasks or exposure to bright light sources between measurement epochs.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout each epoch, the participants remained seated on a wheeled chair to avoid the influence of postural changes on measurements. 34 36 Thereafter the participants relaxed their accommodation by watching a movie binocularly at 5 meters for 15 minutes (accommodation washout), 16 using their habitual distance correction if necessary. Each epoch entailed retinal and choroidal imaging by optical coherence tomography (OCT; SPECTRALIS OCT2 EDI; Heidelberg Engineering, Heidelberg, Germany); measurements of central corneal thickness, corneal radius, anterior chamber depth (ACD), crystalline lens thickness (LT), and AL (IOLMaster 700; Carl Zeiss Meditec AG, Jena, Germany); and intraocular pressure (IOP) (iCare; Tiolat Oy, Helsinki, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…The importance of precise CT measurements to plan keratorefractive surgery and to diagnose and to follow-up glaucomatous patients, made the assessment of this parameter increasingly important in ophthalmological clinical practice [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%